PERKEMBANGAN MORAL REMAJA DI JORONG RUMBAI KECAMATAN MAPAT TUNGGUL KABUPATEN PASAMAN - Mimi Aprilis (Sociocouns: Journal of Islamic Guidance and Counseling, 2022)
This research is focused on the moral development of adolescents in Jorong Rumbai, Mapat Tunggul District. This research is motivated by teenagers who have declining moral development. This study aims to determine the moral development of adolescents in Jorong Rumbai, Mapat Tunggul District, and to describe and analyze the moral development of adolescents in Jorong Rumbai, Mapat Tunggul District. As for the moral development of adolescents there are several phases of adolescent development, namely: (1) stage 1 (levels 1 and 2) pre-conventional stage, (2) stage ii (levels 3 and 4) conventional stage, and (3) stage iii (levels 5 and 6) post-conventional stage. this research is descriptive qualitative, namely a method that describes the conditions that occur in the field in the form of words or not in the form of numbers. The informants in the study were six teenagers in Jorong Rumbai, and six supporting informants were parents of teenagers, and 1 Jorong in Jorong Rumbai. Data collection techniques by making observations or observations and interviews. Based on the results of research that researchers have done on the Moral Development of Adolescents in Jorong Rumbai, Mapat Tunggul District found teenagers who have good and bad morals, teenagers who have good morals can be seen from the way they get along with fellow teenagers, parents, and the community who look good, polite and courteous. Meanwhile, teenagers who have bad morals can be seen from the way they get along with fellow teenagers, parents, and the community who look bad, disobey their parents, don't obey the rules in society, engage in promiscuity such as smoking, drinking alcohol, and using drugs.